A heuristic QoS measurement with domain-based network information model for grid computing environments. (7th May 2010) - Yang, Chao-Tung; Lin, Chih-Hao; Yang, Ming-Feng; Chiang, Wen-Chung
Recently, Grid computing is more and more widespread. Therefore, there exists a common issue, i.e., how to manage and monitor numerous resources of grid computing environments. Mostly, we use Ganglia and Network Weather Service (NWS) to monitor machines' status and network-related information, respectively. But, information provided by Ganglia and NWS is not sufficient in some scenarios owing to varied user requirements. Therefore, we propose a heuristic Quality of Service (QoS) measurement constructed with domain-based information model that provides more effective information to meet user requirements. Furthermore, we expect that users could manage and monitor numerous resources of grid environments more effectively and efficiently.